(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Abstract - Reconstruction of urban waterfronts in St. Petersburg, built in the beginning of the last century, is relevant. In the technical literature and departmental document each type of mooring hydraulic structure has its own method of calculation. Shown the practical implementation of engineering universal method of calculating berthing quays. The proposed generalized model piles in the soil, which under the action of horizontal load rotates as a rigid body and at the same time bends as a flexible rod. Kind of movement depends on the flexural rigidity of the piles and stiffness of the soil. The position of the elastic line of the pile depends on the nature of the upper sealing. The stiffness of soil from the entire cycle, the load on the piles is determined from the сurve the load‒ displacement